Global discontents conversations on the rising threats to democracy - Chomsky, Noam 1928-; Barsamian, David 1945- (The American empire project, 2017)
In wide-ranging interviews with David Barsamian, his longtime interlocutor, Noam Chomsky asks us to consider a world imperiled by climate change and the growing potential for nuclear war. These twelve interviews, conducted from 2013 to 2016, examine the latest developments around the globe: the devastation of Syria, the reach of state surveillance, growing anger over economic inequality, the place of religion in American political culture, and the bitterly contested 2016 U.S. presidential election. In accompanying personal reflections on his Philadelphia childhood and his eighty-seventh birthday, Chomsky also describes his own intellectual journey